Livestock and livelihoods webinar series: Crossroads of animal, human and environment health - International Livestock Research Institute (International Livestock Research Institute, 2021)
Part of the ILRI and Venture 37 Livestock and Livelihoods webinar series, this recording focuses on the crossroads of animal, human and environment health with a focus on scaling up One Health. It was recorded on 21 September 2021.